Analisis konten instagram bupati Banyumas terkait penanganan krisis hoaks Covid-19 - Pundra Rengga Andhita; Rasyid, Muhammad Rafi Ar; Hartanto, Yohanna Tania (Jurnal Studi Komunikasi, 2023)
The problem of the information crisis caused by the Covid-19 hoax has caused several polemics in the Banyumas community. The Covid-19 hoax has made people confused and ignored health protocols. The implication leads to an increase in the death rate in Banyumas. However, this condition was quickly realized by the Ir. Achmad Husein, Regent of Banyumas Regency. Achmad Husein actively clarifies the Covid-19 hoax by uploading content on his Instagram account, namely @ir_achmadhusein. His post shows Achmad Husein's efforts in managing the COVID-19 hoax crisis communication which is quite interesting. This is an important value in this research. Through the Mayring content analysis method, this research dissects the Instagram content of Ir. Achmad Husein, Banyumas Regent, through several units of analysis contained in the Situational Crisis Communication Theory (SCCT). The results showed that the implementation of the three crisis response strategies by Ir. Achmad Husein succeeded in providing comparative and holistic information for the people of Banyumas. Furthermore, through this strategy, Husein also succeeded in turning the information crisis caused by the Covid-19 hoax into a strategic opportunity in building his positive reputation.